On the technology of construction of semi-closed greenhouses of the fifth generation - CHEBANOV, Taras; NOVYY, Volodymyr; SLEPTSOV, Yurii; NOVAC, Tatiana; CHEBANOV, Leonid (Ways to Improve Construction Efficiency, 2024)
The directions and trends of development of protected ground structures at the present stage are robotic greenhouses, nanotechnology, interactive environment, sensor and LED systems, development of cannabis growing technologies, etc. The development of the above directions is facilitated by the fact that large greenhouse complexes have exhausted their resource for further technological and technical development. Such an organization of greenhouse production suffers from large energy and financial losses and poses a serious problem for the environment. The possibilities of vertical greenhouses have been experimentally studied, as well as one of the elements of the pyramid greenhouse – multi-tiered narrow-rack hydroponics. Theoretical studies of sixth-generation greenhouses are being conducted – advanced technological and engineering systems of fully closed greenhouses. Or those in which regulation and changes in microclimate parameters occur using the reserves of the greenhouse's internal space. Without the involvement of external factors. One of the shortcomings of modern greenhouses is the inability to maintain an optimal and high-quality microclimate at certain times of the year. The design and technological features of modern glazed greenhouses of the fifth generation of semi-closed type are considered. Semi-closed type greenhouses allow to ensure high requirements for the microclimate in greenhouses and, accordingly, high yields with lower costs of material resources. A special system regulates humidity in such a way that energy consumption becomes minimal. Even with a strong decrease in the outside air temperature. The system has two fans: supply – air that supplies from the outside to the inside and exhaust, which extracts warm moist air from the greenhouse. The schematic diagrams and calculations of physical processes during the construction and operation of such greenhouses are presented. Ensuring high design requirements for the microclimate in greenhouses (temperature and humidity, carbon dioxide level, air exchange rate - is especially relevant when growing medical cannabis. KNUСA has been conducting research on the technology and mechanization of greenhouse construction for a long time. Special attention is paid to the development of technology for installing frames of such structures, especially light metal greenhouse structures. Technologies are protected by Ukrainian patents for invention.